(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
The main issue in this article is about the rational model and its application in social, political economic directions. In general, a rational model is a quick understanding of the state of internal consciousness, which arises under the influence of an external situation that takes place in our thinking without noticing. A rational model can be the basis of individual behavior. It not only affects the external process, but also contributes to the formation of a person’s consciousness. With the help of this proverb you will get acquainted with the processes of intelligent modeling